The Experience of Victimisation among Muslim Adolescents in the UK: The Effect of Psychological and Religious Factors - Francis, Leslie J. (Religions, 2018)
This study set out to explore the levels of victimisation experienced by Muslim adolescents in the UK, the extent to which victimisation is conceptualised in religious terms, and the extent to which individual differences in the experience of victimisation is related to personal factors, psychological factors and religious factors. Data provided by 335 13- to 15-year-old Muslim students from England, Northern Ireland, Scotland and Wales demonstrated that one in four Muslim students (25%) reported being bullied because of their religion. These students saw their religious identity as being a more important cause of their victimisation than their ethnicity, their colour, or their name. Male and female Muslim students were equally vulnerable to victimisation. Psychological and religious variables predicted individual differences in vulnerability to victimisation among Muslim students.